PENGEMBANGAN SISTEM INFORMASI INDEKSPOTENSI DESABAGI PETUGAS POLISIKEHUTANAN (STUDY KASUS BALAI BESAR TAMAN NASIONAL GUNUNG GEDE PANGRANGO) - Iwan Lesmana; Deni . (NUANSA INFORMATIKA, 2015)
The national park is a nature conservation forest areas which have the goal of protection, research and utilization. During this time, almost all National Parks in Indonesia has the threat of damage from the surrounding rural community in the form of land cultivation, illegal logging, poaching, forest fires, and others are closely related to socioeconomic factors villagers. In order to improve the performance of the forestry police officers for handling forest threat will require an application of the adoption of the Village Potential Index calculation. Where this application can help the forestry police officers for early detection of forest threats. The approach used by the SDLC systems development method of Extreme Programming (XP). System Implementation Village Potential Index is proven to help the Forest Police Officer GPNP in early anticipation of forest threats.Â Keywords : National Parkl, Rural Ability Index,SDLC, Extreme Programing